2019
DOI: 10.2308/jeta-52424
|View full text |Cite
|
Sign up to set email alerts
|

“Alexa, Write an Audit Opinion”: Adopting Intelligent Virtual Assistants in Accounting Workplaces

Abstract: In recent years, there has been exponential growth in the volume of “always listening” intelligent virtual assistant devices used in the home. The adoption of intelligent virtual assistants is also moving rapidly into applications and devices utilized by businesses, including accounting workplaces. Although there are highly publicized drawbacks related to the home-use of this technology, the benefits of this spoken interface are many. Therefore, it is important to review the relevant literature, such as Altman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Conversational commerce has wide applications across industries such as banking, education, entertainment, healthcare, and hospitality (Bolton et al, 2018; Botanalytics, 2018; De Keyser et al, 2019; Lester et al, 2004). Innovations on designing conversational agents for insurance (Riikkinen et al, 2018), transportation and logistics (Hsiao & Chang, 2019), language learning (Dizon, 2017; Fryer et al, 2017), driving assistance (Large et al, 2017), and accounting (Burns & Igou, 2019) have also shown utility in providing customer services in ways that lead to efficient and effective customer experiences and outcomes. However, different conversational agents exist, and the same can be said about industries and service offerings.…”
Section: Reflections and Ways Forward (Rq6)mentioning
confidence: 99%
See 2 more Smart Citations
“…Conversational commerce has wide applications across industries such as banking, education, entertainment, healthcare, and hospitality (Bolton et al, 2018; Botanalytics, 2018; De Keyser et al, 2019; Lester et al, 2004). Innovations on designing conversational agents for insurance (Riikkinen et al, 2018), transportation and logistics (Hsiao & Chang, 2019), language learning (Dizon, 2017; Fryer et al, 2017), driving assistance (Large et al, 2017), and accounting (Burns & Igou, 2019) have also shown utility in providing customer services in ways that lead to efficient and effective customer experiences and outcomes. However, different conversational agents exist, and the same can be said about industries and service offerings.…”
Section: Reflections and Ways Forward (Rq6)mentioning
confidence: 99%
“…Conversational commerce has wide applications across industries such as banking, education, entertainment, healthcare, and hospitality (Bolton et al, 2018;Botanalytics, 2018;De Keyser et al, 2019;Lester et al, 2004). Innovations on designing conversational agents for insurance (Riikkinen et al, 2018), transportation and logistics (Hsiao & Chang, 2019), language learning (Dizon, 2017;Fryer et al, 2017), driving assistance (Large et al, 2017), and accounting (Burns & Igou, 2019) have also shown utility in providing customer services in ways that lead to efficient and effective customer experiences and outcomes. However, different conversational agents exist, and the same can be said about Voice assistants have proliferated increasingly as a result of the emergence of smart speakers, and together, they ease life and form contemporary lifestyles by facilitating various technology-mediated tasks such as ordering food, playing music, and searching a query on the internet, and thus, giving rise to a new form of communication between brands and customers (Smith, 2020).…”
Section: Enabling Designs and Technologies For Conversational Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Competing with companies such as Apple and Google, Amazon was still able to lead the market of conversational agents with around 70% market share (Sciuto et al, 2018). Most businesses started integrating intelligent virtual assistants into their software and electronics (Burns & Igou, 2019). IPAs like Alexa have not only changed the workplace, but also the way people live in their homes.…”
mentioning
confidence: 99%
“… Audit firms invest in more advanced data analytic tools, such as augmented and autonomous AI (see Burns & Igou, 2019). How will these tools impact the nature, extent, and timing of the audit process?…”
Section: Future Research Directionsmentioning
confidence: 99%